Efektifitas Pembentukan Kampung Restorative Justice dalam Penanganan Kasus Pidana di Kejaksaan Negeri Tabanan - Deli Bunga Saravistha; Kadek Dedy Suryana; I Gusti Agung Made Mas Widya Giri Savitri; Shri I Gusti Ngurah Wira Suyasa (Journal of Education and Culture, 2023)
The State of Indonesia is a legal state (rechtsstaat), this has received legitimacy through the provisions of Article 1 Paragraph (3) of the 1945 Constitution of the Republic of Indonesia (1945 Constitution). The Attorney General's Office has issued several policies, including the First, the Attorney General's Regulation of the Republic of Indonesia Number 15 of 2020 concerning Termination of Prosecution Based on Restorative Justice. It is hoped that this provision as a form of prosecution discretion can be used by the Prosecutor to view and balance between the applicable rules and the principle of benefit to be achieved. Diversion and Restorative Justice are the basis for reforming the criminal justice system in the implementation of the juvenile justice system, which can be seen in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, which aims to prevent child offenders from being subjected to punishment or punishment. Both concepts are new things for Indonesian people. Law Number 3 of 1997 does not contain restorative juctice principles, and there are no strict provisions regarding diversion (settlement outside the process). Termination of Prosecution Based on Restorative Justice stipulated in the Attorney General Regulation Number 15 of 2020 guidelines for Public Prosecutors to stop prosecutions with due observance of fairness, public interest, proportionality, punishment as a last resort, and fast, simple and low cost. Socialization Perja 15 of 2020 and updating the role of the prosecutor's office in tackling crime in realizing restorative justice by means of, among other things, making peace efforts and having a peace process where the prosecutor plays an active role in handling cases so that cases can be resolved without having to go to court.